2020
DOI: 10.1186/s13287-020-01682-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of vitronectin in promoting survival of mesenchymal stem cells under serum deprivation stress

Abstract: Background: Due to their immunomodulatory and trophic support functions, mesenchymal stem cells (MSCs) are promising in the field of cell-based regenerative medicine. However, MSC survival post-transplantation is challenged by various microenvironment stress factors. Here, we investigated the role of vitronectin (VTN) in the survival strategy of MSCs under serum deprivation stress condition. Methods: Proliferation kinetics and cell adhesion of MSCs under serum deprivation were determined from population doubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
5
15
0
Order By: Relevance
“…In support, a previous report had shown that growth arrested quiescent human endometrial mesenchymal stem cells were more resistant to heat stress compared to proliferating cells (23). Additionally, earlier report from our lab had also demonstrated the pro-survival effect of VTN in serum deprived WJ-MSCs via mediating G0/G1 cell cycle arrest (16).…”
Section: Discussionsupporting
confidence: 81%
“…In support, a previous report had shown that growth arrested quiescent human endometrial mesenchymal stem cells were more resistant to heat stress compared to proliferating cells (23). Additionally, earlier report from our lab had also demonstrated the pro-survival effect of VTN in serum deprived WJ-MSCs via mediating G0/G1 cell cycle arrest (16).…”
Section: Discussionsupporting
confidence: 81%
“…As reported previously [16], exposure to serum starved condition resulted in flattened morphology with significant increase in cell spread area (data not shown) and cellular adhesion in WJ-MSCs (Fig. 1A, B).…”
Section: Serum Starvation Impairs the Migration Ability Of The Wj-mscssupporting
confidence: 89%
“…Next, we investigated the expression and regulation of VTN under serum starved condition in co-relation with the phenotypic changes observed. In our previous studies [17,18], we had observed that expression of VTN, an ECM component known to be responsible for cell adhesion, was up-regulated under both serum starvation and febrile temperature stress conditions and this was accompanied by increase in cell spread area and cell adhesion. In the present study under serum starved condition, VTN expression again exhibited a strong upregulation both at mRNA and protein levels, though not significant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The loosened-up appearance can explain the appearance of larger size under high and extreme stress. Such phenomenon is also observed in a recent study where cells under serum deprivation exhibit increased cell area [54]. Though no negative impact of stress conditions on spheroid growth is observed, an interesting observation emerges from both individual and combined conditions.…”
Section: Discussionsupporting
confidence: 75%